Hubungan Pengetahuan Dan Pola Konsumsi Fast Food Dengan Status Gizi Pada Anak Sekolah Dasar Di Wilayah Sanur Kaja Denpasar Selatan - Ni Putu Yosi Rahayu; I Komang Agusjaya; A.A Gde Raka Kayanaya (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Technological and socio-economic developments have changed traditional consumption patterns to western consumption patterns such as fast food contains high energy and fat. Based on Riskesdas (2013) the prevalence of obesity is quite high 18,8%. The purpose of this research is to know the relation between knowledge and fast food consumption pattern with nutrition status in elementary school children in Sanur Kaja area. This research type is observational and crossectional design with 76 samples. Data of knowledge collected by angket method, data of fast food consumption pattern collected by interview method using SQ-FFQ, and nutrition status data based on indicator body mass index (IMT/U) collected by anthropometry method. Data analysis uses Pearson correlation statistics. The result of this research showed that 39 (51,3%) samples are knowledgeable enough, consumption patterns of fast food samples both of type, consumption of energy, fat, and frequency more than average, type consumption fast food 47 (61,8%) sample, consumption energy of fast food 42 (55,3%) sample, consumption fat of fast food 40 (52,6%) sample and frequency of fast food consumption 46 (60,5%) sample. The normal nutrition status as much 53 (69,7%) sample, overweight 10 (13,2%) sample, obesity 11 (14,5%) sample, very lean 1 (1,3%) sample and lean 1 (1,3%) sample. Knowledge with fast food consumption pattern and type consumption of fast food with nutrition status there is no significant relationship (p0,05), fast food consumption pattern which includes consumption of energy, consumption of fat and frequency of fast food consumption significant relationship with nutrition status (p 0.05).Keywords: Knowledge, Consumption Pattern, Fast Food, Nutrition Status